Vardopoulos, Ioannis - (:unkn) unknown (My University, 2026)
Studied civil engineering, did his postgraduate studies first in environmental management and conservation and later in sustainable development with honors distinction. Holding a doctorate in applied urban sustainability, he conducts high-quality post doctoral research towards addressing key concerns of the contemporary build environment through principles of applied sustainability. His research interests include a wide range of urban sustainability aspects. www.ivardopoulos.com